2007
DOI: 10.1088/0022-3727/40/6/004
|View full text |Cite
|
Sign up to set email alerts
|

Critical phase transition temperatures of 1–3 type multiferroic composite thin films

Abstract: The critical phase transition temperatures of the ferroelectric (FE) phase and the ferromagnetic (FM) phase in epitaxial 1–3 type multiferroic thin films were obtained based on the thermodynamic model. Analytic expressions of the para–ferro transition temperatures were derived as functions of the volume fraction of the FM phase by considering the effect of the coupled elastic stresses arising from the FE/FM and the film/substrate interfaces. Our results show that the critical temperatures are significantly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…As in composite structures, ferroelectric and magnetic order parameters are coupled, so both ferroelectric and magnetic properties are affected by the increase/decrease of ferroelectric and magnetic material content. This type of behavior, i.e., the increase of ferroelectric T c with increase of magnetic content has also been theoretically predicted for multiferroic composite thin films 45 . For these heterostructures, the increase of ferroelectric Tc shifts towards higher temperature compared to pure PFN may be explained due to the effective misfit strain and ME coupling.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…As in composite structures, ferroelectric and magnetic order parameters are coupled, so both ferroelectric and magnetic properties are affected by the increase/decrease of ferroelectric and magnetic material content. This type of behavior, i.e., the increase of ferroelectric T c with increase of magnetic content has also been theoretically predicted for multiferroic composite thin films 45 . For these heterostructures, the increase of ferroelectric Tc shifts towards higher temperature compared to pure PFN may be explained due to the effective misfit strain and ME coupling.…”
Section: Resultssupporting
confidence: 67%
“…It is also reported that the development of strain, deforms the crystal in the perpendicular direction which provides space for ionic displacement of B site atoms, hence the T c is expected to be modified 48 . In composite structures, the effective misfit strain on ferroelectric material is mechanically transmitted to the magnetic materials through the magnetostrictive effect inducing a change in the magnetic order parameters and T c 45 . Another interesting observation is that another anomaly at ~645 K at 100 kHz begins to develop and becomes prominent as the frequency increases; this is near the magnetic phase transition of the heterostructure.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior, i.e., the increase of ferroelectric T c with increase of magnetic content has been theoretically predicted for 1-3 type multiferroic composite thin films. 40 All the measured thin films exhibit a diffuse (broadening) type of phase transition behavior.…”
Section: Resultsmentioning
confidence: 95%
“…The possible composite architecture depending on the connectivity are: 0-0, 0-1, 1-1, 2-1, 3-1, 3-2, 3-3, 0-2, 1-2, 2-2, and some hybrid architectures, where the number implies the dimension of the magnetic and ferroelectric components, respectively [ 32 , 46 ]. The most commonly used ME architectures with successfully proven enhanced physical properties are: 0-3 particulate composites (where the magnetic nanoparticles (0-dimensional) are dispersed in ferroelectric matrices (three-dimensional)), 1-3 rod composites (where one-dimensional rods are grown in three-dimensional ferroelectric matrix), and 2-2 layered composites (where two-dimensional magnetic thick/thin layers are grown on two-dimensional ferroelectric thin films, and the periodicity might more than one) [ 17 , 32 , 46 , 47 , 48 , 49 ]. Figure 2 shows the 0-3, 1-3, and 2-2 composite nanostructures.…”
Section: Introductionmentioning
confidence: 99%